Decarboxylative Fluorination of Aliphatic Carboxylic Acids via Photoredox Catalysis - Ventre, Sandrine (J Am Chem Soc, 2015)
The direct conversion of aliphatic carboxylic acids to the corresponding alkyl fluorides has been achieved via visible light-promoted photoredox catalysis. This operationally simple, redox-neutral fluorination method is amenable to a wide variety of carboxylic acids. Photon-induced oxidation of carboxylates leads to the formation of carboxyl radicals, which upon rapid CO(2)-extrusion and F(•) transfer from a fluorinating reagent yield the desired fluoroalkanes with high efficiency. Experimental evidence indicates that an oxidative quenching pathway is operable in this broadly applicable fluorination protocol.